Social Exclusion and Hatred Towards Children from Alcoholic Families in Peer Environment. Peculiarities of Pedagogical Support - Mączyńska, Anna (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
The article emphasizes that the family is the main environment of life. If it is a dysfunctional family, all its problems can have a negative impact on the development and upbringing of children. Unfortunately, the key dysfunction in the case of Poland is alcoholism. Therefore, the study emphasizes that the situation of a child growing up in an alcoholic family depends on many factors related to the functioning of the family environment. The addiction of one or both parents, the degree of degradation of family life and the availability of external support are of particular importance here. All of this can lead to social exclusion and hatred of children growing up in families with alcohol problems by their peers. The author proves the need to help children growing up in problematic families, since they are characterized not only by social isolation, but also by bullying or cyberbullying. It is pointed out that the traumatic experience and suffering of such children often go beyond the family environment, where they experience academic failures, difficulties in relationships with peers, etc. The article notes that the consequences of various traumas in the educational or family environment experienced in childhood can have a long-lasting impact on their lives; some of these minors may also become addicted to alcohol, imitating their parents. Therefore, it is important for educators and social workers to develop appropriate strategies for effective psychological and pedagogical support of such families, in particular while raising children.